Versatile Cl-decorated CPM-5 as a blue LED and luminescent sensor for selective Fe3+ sensing and temperature detection. Issue 40 (5th October 2022) - Zhang, Jian-Wei; Yu, Rui-Ying; Li, Xi; Xu, Hai-Qun; Cui, Jin-Hai; Hu, Xin-Cheng; Li, Jie-Qiong
Abstract : A versatile luminescent Cl-decorated CPM-5 was successfully afforded by using a DMF/H2 O/HCl solvent system. Interestingly, the highly stable CPM-5-Cl is suitable for application in Fe 3+ sensing and as a blue LED and ratiometric thermometer. Abstract : The development and utilization of versatile metal–organic framework (MOF) materials for fluorescence applications have received the attention of many researchers. In this study, we constructed a versatile luminescent Cl-decorated CPM-5 (CPM-5-Cl) by employing InCl3 and H3 BTC in a DMF/H2 O/HCl solvent system. The as-synthesized CPM-5-Cl was characterized using PXRD, SEM, EDX mapping, and TGA–DTG. Interestingly, CPM-5-Cl exhibited not only excellent thermal and water stability but also unique solid-state fluorescence emission performance. The CIE coordinate and luminescence photo under UV light indicated CPM-5-Cl as a promising candidate for blue light-emitting diodes. Furthermore, as a ratiometric thermometer, CPM-5-Cl exhibited highly sensitive temperature sensing over a wide temperature range (80–300 K), and the maximum relative sensitivity of CPM-5-Cl reached 3.08% K −1 at 300 K. Moreover, CPM-5-Cl exhibited high selectivity for Fe 3+ detection with low detection limits (2.25 × 10 −4 M) in aqueous solution. It was tested for anti-interference properties, recyclability, and the mechanism of Fe 3+ sensing. Our research provides new opportunities for the design and synthesis of versatile fluorescent In-MOFs.